Unveiling the stealthy tactics: mycoplasma’s immune evasion strategies - Wang, Jingyun; Liang, Keying; Chen, Li; Su, Xiaoling; Liao, Daoyong; Yu, Jianwei; He, Jun (Frontiers in Cellular and Infection Microbiology, 2023)
Mycoplasmas, the smallest known self-replicating organisms, possess a simple structure, lack a cell wall, and have limited metabolic pathways. They are responsible for causing acute or chronic infections in humans and animals, with a significant number of species exhibiting pathogenicity. Although the innate and adaptive immune responses can effectively combat this pathogen, mycoplasmas are capable of persisting in the host, indicating that the immune system fails to eliminate them completely. Recent studies have shed light on the intricate and sophisticated defense mechanisms developed by mycoplasmas during their long-term co-evolution with the host. These evasion strategies encompass various tactics, including invasion, biofilm formation, and modulation of immune responses, such as inhibition of immune cell activity, suppression of immune cell function, and resistance against immune molecules. Additionally, antigen variation and molecular mimicry are also crucial immune evasion strategies. This review comprehensively summarizes the evasion mechanisms employed by mycoplasmas, providing valuable insights into the pathogenesis of mycoplasma infections.